Пошаговое объяснение:
-6(х - 7) = 10 - 5х
-6х + 42 = 10 - 5х
-6х + 5х = 10 - 42
-х = -32
х = 32
9 + (6 + 5х) = -(-2х + 16)
9 + 6 + 5х = 2х - 16
15 + 5х = 2х - 16
5х - 2х = -16 - 15
3х = -31
х = -31 : 3
х = -31/3
х = -10 1/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Пошаговое объяснение:
-6(х - 7) = 10 - 5х
-6х + 42 = 10 - 5х
-6х + 5х = 10 - 42
-х = -32
х = 32
9 + (6 + 5х) = -(-2х + 16)
9 + 6 + 5х = 2х - 16
15 + 5х = 2х - 16
5х - 2х = -16 - 15
3х = -31
х = -31 : 3
х = -31/3
х = -10 1/3